Arguments for and against self and non-self root recognition in plants - Depuydt, Stephen (Frontiers in Plant Science, 2014)
Root–root interaction research gained more and more attention over the past few years. Roots are pivotal for plant survival because they ensure uptake of water and nutrients. Therefore, detection of adjacent roots might lead to competitive advantages. Several lines of experimental evidence suggest that roots have ways to discriminate non-related roots, kin, and – importantly – that they can sense self/non-self roots to avoid intra-plant competition. In this mini-review, the existence of self/non-self recognition in plant roots will be discussed and the current knowledge on the mechanisms that could be involved will be summarized. Although the process of identity recognition is still not completely understood, interesting data are available and emerging new technologies will certainly aid to better understand this research field that can have an important biological, ecological, and agricultural impact.